2022
DOI: 10.54991/jop.2022.35
|View full text |Cite
|
Sign up to set email alerts
|

Perception of climate change from the Himalayan ‘cold desert’ Ladakh, India

Abstract: Climate change perception survey is a method designed to gain insights on people’s perspectives of the changing climate and recognizing important factors, complexities, and limitations towards a climate-conscious conduct. Such surveys are particularly important in ecologically sensitive transitional climatic zones but logistically difficult terrains, where meteorological data is scarce and minor changes in climatic parameters can have unanticipated consequences for the local ecosystem. The current research is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Nr, not reported; Source: Field notes. decreasing trends in snowfall and increasing trend in rainfall with the rise in elevation caused due to temperature increase Wang et al, 2016;Ali et al, 2022;Dong and Ming, 2022;Moazzam et al, 2022) and shortening of winter months. In Hushey and study sites in Leh-Ladakhlocal people reported a decrease in average snowfall and rainfall (except rainfall in very high-altitude site in Leh-Ladakh).…”
Section: Local Perception Of Climate Change Water Related Hazards And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nr, not reported; Source: Field notes. decreasing trends in snowfall and increasing trend in rainfall with the rise in elevation caused due to temperature increase Wang et al, 2016;Ali et al, 2022;Dong and Ming, 2022;Moazzam et al, 2022) and shortening of winter months. In Hushey and study sites in Leh-Ladakhlocal people reported a decrease in average snowfall and rainfall (except rainfall in very high-altitude site in Leh-Ladakh).…”
Section: Local Perception Of Climate Change Water Related Hazards And...mentioning
confidence: 99%
“…In Tissar village of Gilgit-Baltistan, cloudburst induced flash flood in 2014 eroded around 20% agricultural land, and nearly 80% of this damaged land is still barren. At least five major flood events have been reported over the last decade in Leh-Ladakh (Ali et al, 2022). Among them, the cloudburst induced flood in 2010 washed away the trees and bridges and damaged the houses.…”
Section: Frontiers Inmentioning
confidence: 99%